Roles of the Islamic banks in the monetary transmission process in Malaysia - Sukmana, Raditya; Kassim, Salina (Emerald Group Publishing, 2010)

(untitled)
Purpose – This paper aims to determine the importance of the Islamic banks in the monetary transmission process in the Malaysian economy. In particular, the paper analyzes the relevance of Islamic banks’ financing and deposit in channelling the monetary policy effects to the real economy.